Caring for our future : action for Europe's environment. (Office for Official Publications of the European Communities, 1999)
The aim of this publication is to provide the reader with a review of the current state of the environment and the measures taken in this field at European level. It comprises 25 factsheets each dealing with a particular environmental topic. The actions taken by European institutions and the proposals currently under discussion are presented for each issue as well as the responsibilities of the various players involved.